2013
DOI: 10.1002/jsfa.6458
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of Gymnema sylvestre in obesity and diabetes management

Abstract: The prevalence of obesity is associated with many health-related problems. Currently, more than 300 million people are considered to be obese. According to the World Health Organization (WHO), by 2030, 87 and 439 million people will be affected in India and the world, respectively. Today, herbal medicines are gaining interest in the treatment of obesity and diabetes, because of their minimal side effects. Gymnemic acid - an active component isolated from Gymnema sylvestre - has anti-obesity and antidiabetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 37 publications
3
50
0
2
Order By: Relevance
“…More than one billion and 300 million people are considered to be overweight and obese, respectively (Pothuraju et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…More than one billion and 300 million people are considered to be overweight and obese, respectively (Pothuraju et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…These circulatory FFAs further accumulate in several organs (liver, kidney, and muscle), and the development of IR occurs mostly in the muscle tissue. Recent reports suggested that more than 300 and 439 million people are considered to be obese and diabetic, respectively (Pothuraju et al , ).…”
Section: Introductionmentioning
confidence: 97%
“…R. Br. (Family: Asclepiadaceae) is a woody climbing shrub that has medicinal value because of the presence of various bioactive compounds like gymnemic acids (GA) and phenolic compounds (PC), which are used to treat diabetes mellitus [1]. The plant is also used as an ingredient of tea, confections, and many food preparations for the regulation of sugar homeostasis and to control obesity and the level of blood cholesterol [2].…”
Section: Introductionmentioning
confidence: 99%